A smart home system with security and electrical appliances. Issue 2 (17th February 2021) - Chiu, Min-Chie; Lai, Wei-Dian; Chiu, Che-Min
Abstract: As the need for the daily household appliances and home security increases, the application of interaction technologies and electrical appliances used in smart home system has been widely developed. Considering home security, life convenience, and construction cost, a smart home system conjugated with single-chip controlling unit is presented in the paper. The functions of an intelligent home design include daily tasks (cooking, a morning wake-up call) and security mission when residents are not at home. Here, infrared ray sensors used to detect the intruding event are installed onto the entrances (i.e. windows and door). In addition, an IPCAM's motion detecting function is also adopted for intruding event detecting. Considering the entrance convenience (without key) and safe (key losing) when coming home, a vocal identification system in conjunction with keyboard inputting device (an auxiliary device for the vocal identification system) system is adopted in the second generation of smart home system. In order to facilitate the manipulation of the smart home system, an android-based cell phone connected to the microcontroller is also established. And, to assure the home safety, the second lock (lock #2) will be triggered by the user via the cell phone if the intruding event is confirmed. The user can open the optional window to recheck the reality. Moreover, a ventilation system linked to thermal detectors can be automatically triggered via internet. Consequently, "family activity" can be pretended by the audio broadcast system while the house is vacant.